Analisis Penerapan Penyusunan Laporan Keuangan Masjid Baitul Makmur Situbondo Berdasarkan ISAK No.35 - Srirejeki Dwi Krismontiyah; Yulinartati; Nina Martiana (Politeknik Negeri Jember, 2021)
ABSTRACT This study aims to analyze the preparation of the financial statements of the Baitul Makmur Situbondo Mosque based on ISAK No. 35. The type of research used is descriptive qualitative research. Data collection techniques were obtained through observation, interviews and documentation. The data obtained are secondary data and primary data. The results of this study indicate that the mosque's financial statements are not in accordance with ISAK No. 35. Then the mosque's financial statements were reconstructed in accordance with ISAK No. 35 by identifying transactions, making general journals, posting to the general ledger, making trial balances before adjustment, adjusting journals, trial balance after adjustment, preparing financial statements, closing journals, and the post-closing trial balance. And the final results of the accounting process are statements of financial position, statements of comprehensive income, reports of changes in net assets, statements of cash flows, and notes to financial statements.